COMPARATIVE STUDIES ON SEQUENCE, STRUCTURE AND SNPS OF E1 ENVELOPE GLYCOPROTEIN OF CHIKUNGUNYA CIRCULATING IN MAHARASHTRA AND WEST BENGAL STATES OF INDIA - BUDDHADEV MONDAL,; PARTH SARTHI SEN GUPTA,; CHITTRAN ROY,; RIFAT NAWAZ UL ISLAM,; NILADRI HAZRA,; AMAL KUMAR BANDYOPADHYAY, (International Journal of Pharma and Bio Sciences, 2016)
Chikungunya virus (CHIKV) is a female Aedes mosquito-borne alphavirus that recently caused large-scale epidemics of arthritic disease in tropics of Asian region. Molecular substitutions in E1 envelope glycoprotein as well as in other structural and non-structural proteins cause variation in genotypes, infectivity and severity in clinical symptoms. GenBank Isolates AY424803 and KF818473 were associated with epidemics/outbreaks occurred in 1965 and 2012, in Maharashtra and West Bengal states of India respectively. Although E1 glycoprotein based phylogenetic analyses established the former as Asian and the latter as ECSA (East-Central-South-African) genotypes, detailed insight into atomic structures and the effect of acquired mutations of these proteins remain to be worked out. In this study we applied in silico approaches on E1 protein to investigate detailed differential analyses of sequence, atomic model structure and acquired substitutions for their effects on stability and lethality. Physicochemical and sequence studies of these proteins show fine tuning of these properties in reference to the template (3N43). Atomic models remarkably show similar structural features as template including domains topologies, secondary structure arrangements and disulfide bonds. Side chain conformations of models and template, are seen to be similar as both form salt-bridges with almost identical specificity. In silico site directed mutagenesis shows, out of 14 and 2 acquired substitutions in AY424803 and KF818473, only 3 and none are lethal respectively. Our studies provide detailed structural analyses of E1 glycoprotein, new approaches to assess side chain specificity and judgment of lethality of acquired substitutions that have potential applications in interdisciplinary virology.